O naturalismo biológico em John Searle: A objetividade epistêmica e a subjetividade ontológica como artífices da consciência - Brígido, Edimar; Szinwelski, Fátima; Godoi, Felipe (ENDOXA, 2020)
Or present article salient to the theme of consciousness, as a crucial fator we are mindful, based on a historical retake, encompassing the principalities that justify and conceive this phenomenon. Initially, discussed in the "mind-brain" problem, a conscience is given to the leading role of Philosophy of Mind, alicerçada em duas great corntes: monista and dualista. Both, theoretically, from the ramifications of Cartesian thought, which divides the mind and mind into these dichotomous substances or as reduced to pure materialism, discarding subjectivities. Searle, based on his Biological Naturalism, stands out as an innovative thinker, who unleashes the current theories, proposed to analyze two states as a result of epistemic objectivity together with no ontological subjectivity.